2017
DOI: 10.1002/slct.201700244
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Eco–friendly Microwave‐Assisted Synthesis of Silver Nanoparticles using Rosemary Essential Oil as Renewable Reducing Agent.

Abstract: A green and fast methodology was developed to synthesize silver nanoparticles using rosemary essential oil (EO) as a renewable reducing agent. The synthesis process was microwave (MW) assisted, using a coaxial dipole antenna immersed into the reaction medium. This configuration was used to promote both: i) rosemary EO extraction by hydrodistillation, and ii) silver nanoparticle synthesis in an aqueous solution at atmospheric pressure. The effect of two different silver salt substrates and the time reaction on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…It was reported that two important terpenoids, e.g., sesquiterpenoids and monoterpenoids, are basic constituents for the silver nanoparticles' synthesis [71]. Various reports showed the importance of essential oil of different plants' species in the synthesis of silver nanoparticles such as Cocos nucifera [72], rosemary [73], Ricinus communis [74], and Anacardium occidentale [75].…”
Section: Role Of Terpenoids In Green Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…It was reported that two important terpenoids, e.g., sesquiterpenoids and monoterpenoids, are basic constituents for the silver nanoparticles' synthesis [71]. Various reports showed the importance of essential oil of different plants' species in the synthesis of silver nanoparticles such as Cocos nucifera [72], rosemary [73], Ricinus communis [74], and Anacardium occidentale [75].…”
Section: Role Of Terpenoids In Green Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…Silver exhibits higher toxicity to various microorganisms because its attachment to the cell membrane surface significantly impairs proper functions such as respiration and permeability. Several research have used Ag metal as a precursor in the manufacture of nanoparticles [ 13 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. In addition, the gold metal can also be used as a material for making nanoparticles [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microwave (MW) assisted chemical processes are nowadays a mature and well-established research field. Dielectric heating promoted by MW irradiation has been applied to various chemical processes such as reactions, 1 extractions, 2,3 materials synthesis [4][5][6] and biomass processing. 7 MW assisted heating significantly reduces processing time, energy consumption, costs, environmental impact and equipment size with respect to conventional heating methods.…”
Section: Introductionmentioning
confidence: 99%